Surveying the Theory of “Divine Science” in Sheikh Ishraq and Paul Tillich's Views - Muhammad Hussein Kiani; Fatimeh Khafri (آموزه‌‌های فلسفه اسلامي, 2019)
The perspective of Suhrawardi and Paul Tillich can be compared about the divine science from different aspects. In this comparison, there are two aspects of the similarities and two aspects of differences. The aspects of relationships are: at first, both believe in sole meaning of Divine essence (dhat). Both believe in the necessity of the science to essence (dhat), both believe in the necessity of knowledge (the known) in essence (bi dhat) and believe that God by Its Own Essence is knower. This knowledge is also whether knowledge of Himself and of things. The differential aspects are: at first, their approach and base relating to God and God's knowledge of things is dissimilar; meaning, in Tillich's thought, the absolute (pure) Being requires God being non-existent and based on it, the knowledge of God should be thought symbolic and a new meaning for it should be imagined. But in Suhrawardi's thought, God has and existent extra-mental perfection and is existent. Meanwhile, God as the cause of causes ('illat al-'illal) has real knowledge to all things. secodly; the knowledge of pluralities in Tillich's thought does not mean the knowledge to past, present and future but from the view of Suhrawardi, God has been the knower of the origins of things and based on an ‘illuminationist relation’ (al-idafa al-ishraqiyya) He is aware of past, present and future of things by presential knowledge ('ilm huduri).